New U-Pb zircon age constraints for the emplacement of the Reguengos de Monsaraz Massif (Ossa Morena Zone) - Antunes, A. (2012)
The Reguengos de Monsaraz massif is located in the Portuguese sector of the Ossa Morena Zone (ZOM), one of the major geotectonic units of the Iberian Variscan Belt. It intruded Lower Paleozoic metasediments, strongly affected by deformation and metamorphism during the Varis-can orogeny. Pluton emplacement was responsible for the development of a contact metamor-phism aureole in the surrounding country rocks. Based on regional constraints, the intrusion was included in the group of the late-post-tectonic granitoids. The pluton shows an inversely zoned pattern and consists of tonalitic to granodioritic rocks with abundant mafic microgranular enclaves, occupying most of the presently exposed intrusion area and minor bodies of gabbro-diorites in the east and centre. Field, petrographical and geo-chemical data reveal that mixing / mingling between mantle- and crustally-derived magmas and fractional crystallization played a major role in the genesis and evolution of these granitoids 1. Early attempts to date the Reguengos de Monsaraz intrusion, using Rb-Sr isotopic data for a feldspar-amphibole pair from one granodiorite sample, yielded an age of 297.5 ± 2.9 Ma. This age was interpreted as a cooling age and provided a minimum estimate for the timing of mag-matic crystallization. In order to better constrain the age and emplacement sequence of the mas-sif, five samples representing the different magmatic units (gabbro diorites, tonalites and mafic microgranular enclaves) were selected for determination of U-Pb zircon ages by isotope dilution techniques. The zircon populations from two samples of the gabbro diorites (one from the central sector and the other from the easternmost body) yielded overlapping 206Pb/238U average ages of 337.4  1.1 Ma and 338.6 ± 0.7 Ma, respectively. Similar ages were obtained in two samples from the main tonalite-granodiorite facies (337.3 ± 2.3 Ma; 337.8 ± 0.7 Ma). Finally, the zircons from the microgranular enclave yielded a 206Pb/238U average age of 336.5 ± 0.5 Ma. A slightly younger age was obtained in two fractions of titanite from the enclave (333.6 ± 2.5 Ma), suggesting either resetting of their original magmatic ages or late stage crystallization. The new U-Pb age data support a coeval emplacement for all the members of this suite, at ap-proximately 337-338 Ma. Such a close space-time association between mafic and felsic grani-toids is consistent with the proposed mixing model. According to recent studies, this sector of the OMZ was affected by three Variscan deforma-tion events 2. The earlier deformation phases (D1 and D2) occurred in Late Devonian ( 380-360 Ma) and Early Carboniferous times ( 360-345 Ma), whilst the latter (D3) has a Pennsylva-nian age (305-295 Ma). Based on the available geochronological information, the emplacement of the Reguengos de Monsaraz magmas took place at a time of tectonic quiescence between D2 and D3. The relatively young Rb-Sr age recorded in the feldspar-amphibole pair may therefore reflect the effects of the last tectonothermal event, also documented by the replacement of horn-blende crystals by actinolite.